Влияние параметров термокомпрессионной обработки на характеристики качества и износ режущих пластин из сплава Т5К10 при черновом точении катаных заготовок - Сердюк, Ю.Д.; Семижон, О.А.; Прокопив, М.М. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
Results over of research of conformities to law of influence of parameters (pressure of argon, temperature and time of self-control) of process of thermocompression treatment are inprocess brought under constraint argon to 4,5 МПа on the indexes (middle firmness, firmness completely, coefficient of variation) of quality of removable cutting plastins of SNMM 250724 from the alloy of Т5К10 (ГОСТ 19052-82) of production will "Pobedit".